Peningkatan kemampuan komunikasi matematis siswa dengan pembelajaran kooperatif tipe quick on the draw - Agung Saputra; Abdul Rosyid (Program Studi Pendidikan Matematika STKIP Muhammadiyah Kuningan, 2018)
This study aims to determine whether the improvement of students' mathematical communication skills using the quick on the draw cooperative learning model is better than students who use conventional learning models. This type of research is quasi-experimental with the research design of Nonequivalent control group design. The study population was all students of class X Muhammadiyah 2 Kuningan Vocational School 2017/2018 academic year. Sampling is done by purposive sampling technique. The instrument used in this study is a description question to measure students' mathematical communication skills. The increase in communication skills of the experimental class is included in high qualifications while the control class is of low quality. So that it can be concluded that the increase in mathematical communication skills of students who get quick on the draw cooperative learning is better than students who get conventional learning.